Relative abundance, activity patterns and diversity of mammals based on camera trapping data - Nuur Hidayah, Ab Hamid (Universiti Malaysia Sarawak (UNIMAS), 2005)
Camera trapping has recently been introduced as practical method in estimating animal abundance, especially low densities mammals. Based on the data presented from the study conducted at Jerangau Forest Reserve, Terengganu, 30 species of mammal was recorded within the 5940 trap-nights; shows that the area was inhabit by variety of species including large mammals such as elephants, tigers and tapirs. The relative abundance index for each species was calculated based on the total trap nights and the number of independent photos. While the diversity index was calculated using Shannon-Wiener Index and program FORTRAN. Among the species recorded, two ungulates species were most abundance, which are wild boar (RAi= 0.355) and tapir (RAi = 0.152). Analysis of activity patterns shows that 58% of the total independent photos were recorded at night, whereas, 42% were recorded during daytime. The calculation of activity patterns shows that peak activity of tigers was correlated to the peak activity of potential prey species such as wild boar and muntjac.